Prevalence of shingles and its association with PTSD among HIV-infected women in Rwanda. Issue 3 (6th March 2015) - Sinayobye, Jean d'Amour; Hoover, Donald R; Shi, Qiuhu; Mutimura, Eugene; Cohen, Hillel W; Anastos, Kathryn
Abstract : Objective: To examine the prevalence of reported shingles in the last 6 months and its association with post-traumatic stress disorder (PTSD), depression and severity of HIV disease in Rwandan women with HIV. Settings: This cross-sectional study was conducted as part of the Rwanda Women's Interassociation Study and Assessment (RWISA), an observational cohort study designed to assess the impact of HIV and residual factors from experiencing rape in the 1994 genocide in Rwandan women. Participants were recruited through grassroots women's associations of people living with HIV infection and clinical care sites for HIV infection. Most participants (58.5%, n=405/692) had PTSD. Participants: This cross-sectional analysis was conducted in 710 HIV-infected women enrolled in RWISA. Inclusion criteria were: age >15 years, informed consent, HIV test, ability to complete the interview in the local language, travel to and from the research site and participate in a baseline outpatient visit, and being naive to antiretroviral therapy at enrolment. Primary and secondary outcome measures: The outcome of interest was self-reported shingles in the past 6 months. The exposure was PTSD defined using the cross-culturally validated Harvard Trauma Questionnaire. Results: Overall prevalence of reported shingles in the past 6 months was 12.5% (n=89/710). There was an inverse relationship between shingles prevalence and immunological status: 7.6%, 12.3% and 16.7% of women with CD4 >350, 200–350 and <200 cells/µL, respectively, reported singles (p=0.01). In multivariate analysis, PTSD (aOR 1.7; 95% CI 1.02 to 2.89) and low CD4 (aOR 2.4; 95% CI 1.23 to 4.81) were independently associated with reported shingles in the past 6 months. Conclusions: Our study found a significant independent relationship between PTSD and reported shingles, suggesting that PTSD may be associated with immune compromise that can result in herpes zoster reactivation. Further study is needed. It also confirmed previous findings of a strong relationship between shingles and greater immunosuppression in women with HIV infection.